Learnings from providing integrated health, housing and wider care for people rough sleeping during the COVID- 19 pandemic: a national qualitative study of the ‘Everyone In’ policy initiative - Neha Jain; Emma A. Adams; Kate Haddow; Jo Brown; Dan Bleksley; Stephan Morrison; Joanna Kesten; Kelly Howells; Caroline Sanders; Ashley J. Adamson; Eileen Kaner; Sheena E. Ramsay (BMC Health Services Research)
Abstract Background The ‘Everyone In’ national policy initiative launched in England during the COVID- 19 pandemic provided accommodation and health and care support to people who were (or at risk of) sleeping rough. This study aims to understand what worked well and less well in implementing ‘Everyone In’ for improving physical and mental health outcomes for people experiencing homelessness. Methods Between January and October 2023, in-depth interviews/focus groups were conducted across England with those involved in the delivery/implementation of ‘Everyone In’ and those accommodated. Framework analysis and case study analysis were used for a contextual understanding of the implementation of the policy initiative. Results Twenty-five people accommodated through ‘Everyone In’ (28–58 years; 88% males) and 43 service providers (25–62 years; 40% males) were interviewed. Flexibility in funding and resources, ‘joining up’ services/support, and innovative responsiveness in services across health, care, and housing systems were key positive features of the initiative. In the long term, ‘Everyone In’ has provided positive learnings for delivering holistic and integrated health and social care. It has also highlighted the importance of accommodating psychosocial needs and addressing the complexities of alcohol and substance use in all homelessness strategies. Conclusions Pathways to care for people experiencing homelessness need to be flexible and responsive. Complexities such as substance use need to be approached with compassion while addressing the role of wider determinants in such health behaviours. Innovative approaches and joined-up work improve delivery of interventions and integrated care can reduce barriers to access to support.